Social issue, childhood and vocational education. The Salesians and the option for the poorest. Cordoba, Argentina, 1905-1935 (Quinto Sol, 2017)
By the early 20th century, the Salesians carried out an educational work of strong social content, dedicated to professional and moral formation of children and youth at risk, which were considered one of the most pressing social issues. Through analysis of the student group formed in the classrooms and workshops of the Salesian School of Arts and Crafts, this paper discusses the experience of this group of children, with the intention to approach different situations of vulnerability experienced by a significant portion of children in Córdoba, during the liberal modernity.
Keywords: social issue; poor childhood; labour education; salesianos; Córdoba